What, if anything, is a caesura? The ontology of the 'pause' in English heroic verse. (August 2019) - Groves, Peter
The term 'caesura' (or 'pause') has featured in discussion of English iambic pentameter for four centuries, and yet it still lacks what the Latin hexameter or the French alexandrine have: a definition of the term that might be usefully applied in stylistic description. Despite the temptation to dismiss it as a prosodic chimera or a mere epiphenomenon of syntax, this article will investigate a rough consensus that emerged amongst 18th-century theorists and practitioners about the bisecting caesura as both a normative element of versification and an aesthetic instrument, and attempt to formalize that consensus into a taxonomy based on linguistic features that will allow the caesura to function as a feature of stylistic description and analysis, not just for the heroic couplet but for the pentameter more generally, in terms of three independent and objectively definable properties that I term 'balance', 'juncture' and 'integration'.